Study the Influence of number of laser pulses on Optical Properties of CdS Thin Films Prepared by Laser Pulsed Deposition - Khaldoon Jasim. Mohammed; Manal Merzah. Hadi (African Journal of Advanced Pure and Applied Sciences, 2022)
In this paper, we studied the effects of the number of laser pulses and optical properties, such as the UV-visible spectra of cadmium sulfide (CdS). The films were created using the pules laser deposition technique (PLD) in a vacuum at a pressure of 10-5 mbar at a wavelength of 1064 nm with various laser pulse numbers (50, 100, 150, and 200) and a frequency of 6 Hz, with a laser energy of 700 mJ. The optical properties of the films were studied, and the variables affecting them were investigated in relation to the number of laser pulses. In the visible region, the average transmittance of cadmium sulfide (CdS) thin film was found to be more than 70%. We discovered that as the number of laser pulses increases, so does the transmission of the film, and that all films have a value of absorption coefficient (> 104 cm1), which increases the probability of the occurrence of allowed direct transitions with band gap. The purpose of this work was to investigate the effect of the number of laser pulses on certain optical properties of pulsed laser deposition (PLD) techniques on 25- K deposited CdS films.